Environmental sustainability change management in SMEs: learning from sustainability champions. (25th January 2012) - Chadee, Doren; Wiesner, Retha; Roxas, Banjo
This study identifies the change management processes involved in undertaking environmental sustainability (ES) initiatives within Small and Medium Size Enterprises (SMEs) and relate these to the main attributes of learning organisations. Using case study techniques, the study draws from the change management experiences of a sample of 12 ES champions in different industries. The findings suggest that the ES champions experience four distinct change management stages in undertaking ES initiatives; namely the design, internalise, implement and evaluate stages. Each stage is also found to relate strongly with a number of key characteristics of learning organisations. Overall, the findings suggest that SMEs with strong learning organisation attributes are more likely to be successful in implementing and managing ES change initiatives. The implications of the findings are also discussed.